2023
DOI: 10.1038/s41467-023-39090-4
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal or airborne transmission-mediated delivery of an attenuated SARS-CoV-2 protects Syrian hamsters against new variants

Abstract: Detection of secretory antibodies in the airway is highly desirable when evaluating mucosal protection by vaccines against a respiratory virus, such as the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We show that intranasal delivery of an attenuated SARS-CoV-2 (Nsp1-K164A/H165A) induces both mucosal and systemic IgA and IgG in male Syrian hamsters. Interestingly, either direct intranasal immunization or airborne transmission-mediated delivery of Nsp1-K164A/H165A in Syrian hamsters offers prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Near-universal population immunity to SARS-CoV-2 may somewhat mitigate the safety concerns of using LAV in immune-competent individuals as a booster against emerging variants. In support, we have shown previously (22,23) that LAV can boost heterotypic nAbs in previously vaccinated hamsters. Similarly, another research group in Syrian hamster model with an LAV candidate (sCPD9) also shown vaccinated animals developing robust nAbs against heterologous SARS-CoV-2 challenge (24).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Near-universal population immunity to SARS-CoV-2 may somewhat mitigate the safety concerns of using LAV in immune-competent individuals as a booster against emerging variants. In support, we have shown previously (22,23) that LAV can boost heterotypic nAbs in previously vaccinated hamsters. Similarly, another research group in Syrian hamster model with an LAV candidate (sCPD9) also shown vaccinated animals developing robust nAbs against heterologous SARS-CoV-2 challenge (24).…”
Section: Discussionsupporting
confidence: 81%
“…To determine if a vaccine designed against an ancestral virus may protect against contemporary variants, we tested our LAVs in Syrian hamsters, which are highly susceptible to SARS-CoV-2 and have been widely used in COVID-19 research (23,(19) . Besides the prototype WA1-based LAV, we also generated additional attenuated viruses with the WA1 spike replaced with BA.1, BA.2 or BA.5 spike protein, namely BA.1-LAV, BA.2-LAV, and BA.5-LAV (23). We vaccinated male adult Syrian hamsters with a single, low dose (100 PFU) of LAVs bearing WA1 spike, BA.5 spike or mixed LAV (WA1 + BA.1 + BA.2 + BA.5) (Fig.…”
Section: Cross Protectivity Conferred By Candidate Live Attenuated Va...mentioning
confidence: 99%
“…The Vero E6 cell line (Cat # CRL-1586) was purchased from American Type Culture Collection (ATCC) and cultured in Dulbecco’s minimal essential medium (MEM) supplemented with 10% fetal bovine serum (FBS) (Invitrogen) and 1% penicillin/streptomycin and L-glutamine. The H1299-hACE2 cell line stably expressing human ACE2 was previously generated by lentiviral transduction of the NCI-1299 human lung carcinoma cell line (ATCC CRL-5803) with pLVX-hACE2 and selected with 1 mg/mL puromycin 60 . H1299-hACE2 cells were maintained in DMEM supplemented with 5% penicillin and streptomycin, and 10% FBS at 37°C with 5% CO2.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, vaccination of golden Syrian hamsters with only 100 plaque forming units (PFU) of the attenuated WA1-ΔPRRA-ΔORF6-8-Nsp1 K164A/H165A induced strong humoral responses and protected against WT SARS-CoV-2-induced weight loss and pneumonia ( Liu et al., 2022b ). In a more recent study, the authors showed that intranasal inoculation with this attenuated SARS-CoV-2 induced both mucosal and systemic IgA and IgG responses in golden Syrian hamsters ( Stauft et al., 2023 ).…”
Section: Iav Ns1 and Sars-cov-2 Nsp1 As Targets For Vaccine Developmentmentioning
confidence: 99%
“…Interestingly, either direct intranasal vaccination or airborne transmission-mediated delivery of WA1-ΔPRRA-ΔORF6-8-Nsp1 K164A/H165A protected against heterologous challenge with different SARS-CoV-2 variants of concern (VoC), including Delta, Omicron BA.1, Omicron BA.2.12.1, and Omicron BA.5 ( Stauft et al., 2023 ). Reduced levels of viral replication and lung inflammation were observed in vaccinated animals, demonstrating the feasibility of implementing WA1-ΔPRRA-ΔORF6-8-Nsp1 K164A/H165A as a safe, immunogenic, and protective nasal LAV to protect against SARS-CoV-2 infections, including recently circulating VoC ( Stauft et al., 2023 ). This emphasizes the possibility of including modifications in SARS-CoV-2 Nsp1 that impair its ability to inhibit host gene expression for the development of safe, immunogenic, and protective LAV for the prophylactic treatment of SARS-CoV-2 infections, similar to IAV NS1.…”
Section: Iav Ns1 and Sars-cov-2 Nsp1 As Targets For Vaccine Developmentmentioning
confidence: 99%